Dampak Pencemaran Udara terhadap Kesehatan Masyarakat di Perkotaan - Rosatul Umah; Eva Gusmira (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Urban air pollution is a critical environmental issue, significantly impacting public health. This study examines the sources of urban air pollution, types of pollutants, and their health effects. Methods include literature review and analysis of health data from urban populations. Findings reveal that exposure to pollutants such as PM2.5, NO2, and O3 leads to respiratory and cardiovascular diseases, reduced lung function, and increased mortality rates. The study highlights the need for sustainable urban planning and stringent emission control measures to mitigate these health risks. Implications suggest that policy interventions and public awareness are crucial in addressing the adverse health impacts of urban air pollution.